Bagaimana Mengembangkan Industri Fintech Syariah di Indonesia? Pendekatan Interpretive Structural Model (ISM) - Aam Slamet Rusydiana (AL-MUZARA'AH, 2018)
Fintech in Indonesia is an untapped market opportunity. As a country with the largest muslim population in the world, the prospect of Islamic fintech in Indonesia is very good. This study tries to answer the problems that occur, strategy, and stakeholders involved in developing Islamic fintech in Indonesia using the Interpretive Structural Model (ISM) approach. The core problem faced in developing the Islamic finance technology industry is the lack of policy instruments that maintain the work process of fintech and the availability of human resources for fintech. The strategy needed in the framework of developing Islamic fintech is the ability to manage and analyze data in the big data era and human resources in digital marketing. For ecosystem aspects or actors involved in developing Islamic fintech in Indonesia, important actors include government or regulators, educational institutions (universities), as well as existing industries (banks and other financial institutions).